2020
DOI: 10.55056/cte.412
|View full text |Cite
|
Sign up to set email alerts
|

Technologies of distance learning for programming basics on the principles of integrated development of key competences

Abstract: In the era of the fourth industrial revolution – Industry 4.0 – developing key competences (digital, multilingual and mathematical competences in particular) is of paramount importance. The purpose of this work is to investigate the content of key competences of a secondary school student and to develop a method of teaching for the integrated development of multilingual and mathematical competences in the process of teaching Programming Basics with the help of distant technologies. The objectives of the resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 11 publications
0
21
0
Order By: Relevance
“…In Ukraine, there are scientific schools that explore the possibilities of distance education and the principles of its organization. Researches of Bobyliev and Vihrova [4], Franchuk and Prydacha [9], Havrilova et al [15], Hniedkova [16] Kozlovsky and Kravtsov [26], Kravtsova, Kaminska and Kravtsov [27], Kukharenko and Oleinik [28], Kushnir et al [30], Lénárt [31], Petrenko et al [39], Polhun et al [40], Prokhorov et al [42], Shokaliuk et al [45], Syvyi et al [48], Tarasov et al [49], Vakaliuk et al [54], Yahupov, Kyva and Zaselskiy [62], Zinovieva et al [63,64] and others devoted to development of distance learning methodologies and distance learning systems.…”
Section: Related Workmentioning
confidence: 99%
“…In Ukraine, there are scientific schools that explore the possibilities of distance education and the principles of its organization. Researches of Bobyliev and Vihrova [4], Franchuk and Prydacha [9], Havrilova et al [15], Hniedkova [16] Kozlovsky and Kravtsov [26], Kravtsova, Kaminska and Kravtsov [27], Kukharenko and Oleinik [28], Kushnir et al [30], Lénárt [31], Petrenko et al [39], Polhun et al [40], Prokhorov et al [42], Shokaliuk et al [45], Syvyi et al [48], Tarasov et al [49], Vakaliuk et al [54], Yahupov, Kyva and Zaselskiy [62], Zinovieva et al [63,64] and others devoted to development of distance learning methodologies and distance learning systems.…”
Section: Related Workmentioning
confidence: 99%
“…Distance education servers to gain students' knowledge and the academic staff skills and proficiency using ICT independently from external factors [14,28]. The important feature of e-learning and distance education is the active involvement of students into educational process [4,31,35,39]. They become active collaborators instead of passive learners, when teacher plays the role of guide and even advisor rather that instructor.…”
Section: Introductionmentioning
confidence: 99%
“…Our studies have shown that the problem of digital and informational competence formation was engaged in Svitlana M. Amelina [1], Albert A. Azaryan [59], Zinaida P. Bakum [2], Nadiia R. Balyk [7], Olga V. Bondarenko [19], Valerii Yu. Bykov [9], Olean O. Gritsenchuk [45], Anna V. Iatsyshin [28], Alla A. Kharkivska [18], Hennadiy M. Kravtsov [23], Olena H. Kuzminska [27], Svitlana H. Lytvynova [30], Oleksandr S. Martyniuk [25], Mariia S. Mazorchuk [47], Yevhenii O. Modlo [36], Natalia V. Moiseienko [37], Yuliia H. Nosenko [39], Oksana V. Ovcharuk [44], Svitlana V. Shokaliuk [53], Nataliia V. Soroko [55], Andrii M. Striuk [56], Svitlana O. Sysoieva [57], Rostyslav O. Tarasenko [58], Iryna M. Trubavina [61], Kateryna V. Vlasenko [65], Vasyl V. Yahupov [66] and others.…”
Section: Introductionmentioning
confidence: 99%